MARKETING EFFORTS TO IMPROVE PERFORMANCE EMPOWERMENT THROUGH QUALITY PRODUCT PORTFOLIO (Study on Counter Handhphone And Pulses In Semarang) - Sinar Hubtriyan Ade (JURNAL STIE SEMARANG, 2017)
ABSTRACT This research departs from the empirical contradiction, the first few studies on the relationship with the consumer orientation of marketing performance, particularly with regard to form business relationships counter handphone. Secondly there was controversy over the results of previous studies on the relationship between customer orientation with performance marketing. In addition there are the problems faced by mobile counters and pulse in Semarang is marketing performance is not optimal, causing a decrease in the number of outlets in Semarang significantly over the last five years. In this study population was the whole counter handphone and pulses in Semarang that in the period 2015 amounted to 1,446 outlets and is being added every month the amount is known from PT. MULTIKOM Indonesia. The sample used 150 outlets in Semarang, samples were taken using accidental sampling method by distributing evenly in each region in order to obtain optimal results.SEM analysis tool. The results of the study to get a result if (1) the consumer orientation does not affect the quality of the product portfolio. (2) consumer orientation significantly influence the effectiveness of the selling-in. (3) the breadth of networking supplier does not affect the effectiveness of the selling-in. (4) the effectiveness of selling in a significant effect on the quality of the portfolio. (5) consumer orientation does not affect the performance marketing. (6) the effectiveness in selling significant effect on marketing performance. (7) the quality of the product portfolio significantly influence marketing performance. Keywords: empowering product portfolio quality and marketing performance ABSTRAK Penelitian ini berangkat dari adanya kontradiksi empiris, pertama masih sedikit penelitian tentang hubungan orientasi konsumen dengan kinerja pemasaran, khususnya yang terkait dengan bentuk hubungan bisnis counter handphone. Kedua terdapat kontroversi hasil penelitian terdahulu mengenai hubungan antara orientasi konsumen dengan kinerja pemasaran. Selain itu terdapat permasalahan yang dihadapi counter handphone dan pulsa di Semarang adalah kinerja pemasaran yang tidak optimal sehingga menyebabkan penurunan jumlah outlet di Semarang secara signifikan selama lima Tahun terakhir Dalam penelitian ini populasinya adalah seluruh counter handphone dan pulsa di Semarang yang pada periode Tahun 2015 berjumlah 1.446 outlet dan selalu bertambah setiap bulannya yang jumlahnya diketahui dari PT. Multikom Indonesia. Sampel yang digunakan 150 outlet di Semarang, Pengambilan sampel menggunakan metode accidental sampling dengan cara penyebaran merata di setiap wilayah agar mendapatkan hasil yang optimal. Alat analisis menggunakan SEM. Hasil penelitian mendapatkan hasil jika (1) orientasi konsumen tidak berpengaruh terhadap kualitas portofolio produk.(2) orientasi konsumen berpengaruh signifikan terhadap efektifitas selling-in. (3) keluasan jejaring pemasok tidak berpengaruh terhadap efektifitas selling-in. (4) efektifitas selling-in berpengaruh signifikan terhadap kualitas portofolio. (5) orientasi konsumen tidak berpengaruh terhadap kinerja pemasaran. (6) efektifitas selling-in berpengaruh signifikan terhadap kinerja pemasaran. (7) kualitas portofolio produk berpengaruh signifikan terhadap kinerja pemasaran. Kata kunci: pemberdayaan kualitas portofolio produk dan kinerja pemasaran